2022
DOI: 10.1002/rth2.12809
|View full text |Cite|
|
Sign up to set email alerts
|

Lupus anticoagulant associates with thrombosis in patients with COVID‐19 admitted to intensive care units: A retrospective cohort study

Abstract: Background Thrombosis is a frequent and severe complication in patients with coronavirus disease 2019 (COVID‐19) admitted to the intensive care unit (ICU). Lupus anticoagulant (LA) is a strong acquired risk factor for thrombosis in various diseases and is frequently observed in patients with COVID‐19. Whether LA is associated with thrombosis in patients with severe COVID‐19 is currently unclear. Objective To investigate if LA is associated with thrombosis in critically ill patients with COVID‐19. Patients/Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Noteworthy, the levels of b2GPI in COVID-19 patients were lower than in the healthy population. A few previous studies have reported contradicting results on the prevalence of aPL in COVID-19-associated thrombosis, partly because of differences in patients' backgrounds and the type of aPL measured (13,32,33). Some retrospective cohort studies have reported a higher prevalence of aPL in critically ill COVID-19 patients (34) than in non-severe patients (13,18).…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthy, the levels of b2GPI in COVID-19 patients were lower than in the healthy population. A few previous studies have reported contradicting results on the prevalence of aPL in COVID-19-associated thrombosis, partly because of differences in patients' backgrounds and the type of aPL measured (13,32,33). Some retrospective cohort studies have reported a higher prevalence of aPL in critically ill COVID-19 patients (34) than in non-severe patients (13,18).…”
Section: Discussionmentioning
confidence: 99%
“…Antiphospholipid antibodies have been described in many series of patients with COVID-19 73 ; their presence may be associated with disease severity, 74 though their clinical impact on the incidence of thrombosis or the outcome of a COVID-19 infection remains uncertain. 75 , 76 However, IgG isolated from patients with COVID-19 has been shown to activate neutrophils, induce release of neutrophil extracellular traps, and stimulate thrombosis in mice. 64 , 77 In contrast, there is, to this point, little information available concerning antiphospholipid antibodies in the post-COVID syndrome.…”
Section: Pathogenic Theories In Pascmentioning
confidence: 99%
“…In Noordermeer et al (2002) 1 the journal has been informed that Professor M.A. Spruit was incorrectly included as a collaborator on the Dutch COVID & Thrombosis Coalition (DCTC) in the Acknowledgements section of this article.…”
mentioning
confidence: 99%